Tactical decision-making in sport. How coaches can help athletes to make better in-games decisison (Routledge, 2020)
This book expands on the `Developing Thinking Players` model across a wide range of team and individual sports, to explain how coaches can help athletes to learn how to make better decisions during play and to think for themselves. It provides an overview of game-centred and athlete-centred approaches to teaching and coaching in sport, combining essential theory with practical tips and guidance.